“Am I Man Enough?”: Diskriminasi terhadap Identitas Transpria Muda (Studi Analisis Video YouTube Trans Men Talk Indonesia) - Himas Nur Rahmawati (Universitas Gadjah Mada, 2021)
Discourse contestation around youth in Indonesia still rarely touches issues related to gender minority identities, transman (transgender man) is one of them. This research discusses the complexity of the problems and situations of discrimination experienced by young transmen in Indonesia. The research was conducted by analyzing the YouTube video of Trans Men Talk Indonesia entitled